Impacts of work environment and family-work resource spillover on employees' creativity at work place in the Ethiopian Institute of Agricultural Research - Yohannes Mekonnen Yesuf; Demis Alamirew Getahun; Asemamaw Tilahun Debas (Cogent Business & Management, 2024)
A crucial component of creativity is regarded as a prized asset for long-term corporate success and sustainable competitiveness. As a result, not only academic scholars and policy experts but also business leaders have given the topic more attention. The study of creativity is a dynamic, expanding subject of study. This study presents a conceptual model that examines the impact of the work environment and family-work resource spillover on employees' creativity. The analysis is based on Amabile and Pratt's `dynamic componential model of creativity and innovation in organizations' combined with Greenhaus et al.'s `family-work enrichment theory.' Partial Least Squares (PLS) path modeling in SmartPLS 4 was used to empirically test the proposed hypotheses. The data were collected from 302 researchers working with the agricultural research institute in different centers in Ethiopia. The findings suggested the significantly positive direct impacts of work group support, managerial encouragement, organizational encouragement, a lack of organizational impediments, and family-work resource spillover on employees' creativity. However, the results did not confirm the direct relationships between sufficient resources, reliable workload pressure, freedom, challenging work, and employees' creativity. The study provides empirical evidence in the context of the EIAR and delivers solid theoretical and practical implications to experts, leaders, and policymakers. Finally, this study provides a robust mechanism for leaders at agricultural research institutes to develop strategies for enhancing employees' creativity in the workplace.
Keywords: 650; creativity; work environment and family-work resource spillover